(untitled) (Perner’s Contacts, 2015)
As it is difficult to monitor and evaluate the state of operated oil effectively based on individual determinations of many of its tribodiagnostic parameters (TDP), a possibility of processing the procedure of selected methods of multidimensional statistical analysis - principal component analysis (PCA) on the matrix of tribodiagnostic data of worn-out OA-M6 ADS II engine oil and discriminant analysis (DA) – was tried.